2000
DOI: 10.2337/diacare.23.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Influence of caffeine on the frequency and perception of hypoglycemia in free-living patients with type 1 diabetes.

Abstract: Figure 3-Change in middle cerebral artery blood velocity during caffeine and placebo supplementation compared with baseline. Male patients (A) and female patients ( B).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…Long-term use of theophylline (and related methylxanthine derivatives) is subject to the emergence of tolerance for many of its effects (31). Although there are indications that tolerance remains incomplete under hypoglycemic conditions (12), this issue needs to be further explored. Appropriate studies are therefore required to establish the clinical potential of theophylline in the management of hypoglycemia unawareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term use of theophylline (and related methylxanthine derivatives) is subject to the emergence of tolerance for many of its effects (31). Although there are indications that tolerance remains incomplete under hypoglycemic conditions (12), this issue needs to be further explored. Appropriate studies are therefore required to establish the clinical potential of theophylline in the management of hypoglycemia unawareness.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, by blocking adenosine-induced maintenance of vascular tone, they reduce cerebral blood flow (CBF), enabling faster perception of decreasing plasma glucose levels and earlier initiation of metabolic and symptom responses. The concept of improved hypoglycemia awareness by adenosine-receptor antagonism has already been successfully tested in humans (9,11,12). However, studies in type 1 diabetic patients with proven hypoglycemia unawareness are still lacking.…”
mentioning
confidence: 99%
“…Previously we have shown that ingestion of modest amounts of caffeine (equivalent to three to four cups of dripbrewed coffee each day) augments the symptomatic and hormonal responses to hypoglycemia in healthy volunteers (15) and patients with type 1 diabetes (6). The beneficial effect of caffeine on hypoglycemia risk is independent of a change in glycemic control (16). Here, using continuous interstitial glucose monitoring, we have shown that caffeine may also be beneficial by reducing the frequency of moderate episodes (Ͻ53 mg/dl) of hypoglycemia occurring at night.…”
Section: Resultsmentioning
confidence: 82%
“…In a recent report, administration of caffeine increased blood glucose concentrations during the day and augmented postprandial glucose levels when habitual coffee drinkers with type 2 diabetes were monitored during daily life (Lane et al, 2007). In contrast, other studies reported that caffeine substantially lowered the risk of clinical type 2 diabetes (Debrah et al, 1996;Watson and Kerr, 1999;Watson et al, 2000;van dam and Feskens, 2002). Although the influence of caffeine in normal adults and diabetics has been studied, the results are clearly controversial.…”
Section: Discussionmentioning
confidence: 86%